Mid-Arm Circumference and Triceps Skin-Fold Thickness in Rural School Children: A Cross Sectional Study - Kolekar, Sunil M.; Sawant, Sunita U. (Issues and Development in Health Research Vol. 4, 2021)
The mid-arm circumference and triceps skin-fold thickness in rural schoolchildren aged 5 to 13 years were investigated in a cross-sectional study. The research was conducted in Maharashtra, India, at Sangli district schools. A total of 910 students from rural schools (500 boys and 410 girls) were studied. Mid-arm circumference provides overall information regarding the status of muscle development. Girls in rural schools had higher mid-arm circumferences and triceps skin-fold thicknesses than boys. As there was no established Indian norm for mid-arm circumference, the results of this study were compared to those of other researchers who conducted their research in well-nourished and affluent schoolchildren who were not limited in their growth by malnutrition or infection. Rural schoolchildren had smaller mid-arm circumference and triceps skin-fold thickness than well-fed, affluent schoolchildren, which might be linked to the latter's improved socioeconomic standing.